Catabolism of amino acids in severe burn disease - E. I. Vereshchagin; I. M. Mitrofanov; R. I. Seliverstov; I. V. Peshkova; I. Yu. Samatov; E. I. Streltsova; V. N. Kokhno (Сибирский научный медицинский журнал, 2025)
The severity of the catabolic syndrome for burn disease determines the outcome along with the course of shock and immunosuppression, so correction of protein-energy deficiency is an important part of intensive care. The changes in nucleic acid metabolism in patients with severe burn injury that we noted earlier can be the cause of the development and maintenance of catabolic syndrome.   The aim of the work was an objective assessment of the relationship between the nucleic acids exchange and the amino acids catabolism in severe burn trauma.   Material and methods. 40 patients of both sexes aged 18–70 years with severe burn injury were included in the study: burn of II–III degree with a total area of more than 40 % (and a deep burn area of > 20 %), who had been in the intensive care unit for burn injuries for more than three days after trauma. The first group included surviving patients (30 people), the second – deceased patients (10 people).   Results. Significant increase in the level of blood urea was observed starting from the third day of trauma in all patients. In the first group, the blood urea/creatinine ratio on the third day was 0.073 ± 0.007, with a significant increase from the fifth day, and a further increase on the tenth day to 0.124 ± 0.010, i.e. 1.7 times (p = 0.0002). Hypourecemia (decrease in serum uric acid less than 200 μmol/l) was observed in almost all patients, with a maximum decrease on the seventh and tenth days (142.7 ± 9.0 and 139.0 ± 7.5 μmol/l, respectively). It is characteristic that the maximum changes in the blood urea/creatinine ratio and hypourecemia coincided in time. To clarify the relationship between amino acid catabolism and nucleic acid metabolism, a correlation analysis was carried out between the excretion of urea nitrogen and the level of serum uric acid in the first group patients. The analysis showed a significant correlation between the daily excretion of urea nitrogen on the seventh day, and the level of serum uric acid on the third day (r = 0.66, p = 0.0392) and on the tenth day (r = –0.66, p = 0.0376). Considering the revealed relationship, the informative value of the ratio of blood urea/uric acid was assessed. The value of this index in the first group on the third day of observation was 0.032 ± 0.006, with a significant increase to the seventh (0.07 ± 0.010, p = 0.0002) and tenth days (0.072 ± 0.007, p = 0.0002), i.e. more than 2 times.   Conclusions. An increase in amino acid catabolism occurs almost simultaneously with changes in nucleotide metabolism, with maximum changes on the seventh and tenth days after burn injury. A significant correlation was noted between the daily urea nitrogen excretion and the level of serum uric acid in the first tenth days after a severe burn injury. The results obtained indicate that an increase in amino acid catabolism may also be associated with changes in the metabolism of nucleic acids in a critical condition.